Major unsolved points in adult neurogenesis: doors open on a translational future? - Peretto, Paolo; Bonfanti, Luca (Frontiers in Neuroscience, 2014)
The ultimate goal of exploiting adult neurogenesis (AN) as a source of cell replacement is far from being achieved. In spite of many data gathered during the last two decades on homeostatic and reactive neurogenesis, it is evident that such knowledge is not sufficient for granting translational outcomes. By asking the question whether AN research field has to be considered as a dead end in such a perspective, here we review some major unresolved issues: multifaceted evolutionary constraints emerged in mammals, stem/progenitor cell type/availability and tissue permissivity, the possible impact on other brain functions and/or interplay with other forms of plasticity, and relevance in humans. We suggest that full understanding of AN biological processes is an essential step to their possible exploitation for brain repair, and that further fundamental, multidisciplinary research is required before translational outcomes can be reached. Scientist's attitude and their communication skills are also important. To avoid overestimation of AN reparative potential, more distant goals of cell replacement should be kept clearly distinct from restorative approaches involving AN plasticity, both representing translational perspectives.